Pertanggungjawaban Hukum Terhadap Pelaku Usaha Yang Menggunakan Bahan Kimia Melebihi Standar Dalam Produk Skincare - Janneta Angela Pangalila; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Fakultas Hukum Universitas Warmadewa, 2024)
The existence of skincare products as a necessity is in great demand by the public, but the existence of this online media problems can arise because they do not care about the ingredients in skincare products such as ingredients exceeding the standard, namely mercury can damage skin cells. The formulation of this problem, 1) How is the legal regulation of business actors who use chemicals exceeding standards in skincare products to avoid harm to consumers in Indonesia? and 2) How is legal responsibility for business actors who use chemicals exceeding standards in skincare products that harm consumers in Indonesia? This research uses normative legal research and doctrinal law as well as statutory and conceptual approaches. The conclusion of this study is that the legal regulation of Article 4 letter c, Article 7 letter a, d, Article 8 paragraph (1) of the GCPL Law, Article 196 of the Health Law and Article 8 of BPOM Regulation No. 17 of 2022. The legal responsibility is based on Article 19 of the GCPL. Suggestions to the government should better supervise the circulation of skincare products that use chemicals that exceed the standard because if more and more circulate, consumers will be harmed.